2013
DOI: 10.1242/jcs.120261
|View full text |Cite
|
Sign up to set email alerts
|

The IGFBP7 homolog Imp-L2 promotes insulin signaling in distinct neurons of the Drosophila brain

Abstract: SummaryIn Drosophila, Insulin-like peptide 2 (Dilp-2) is expressed by insulin-producing cells in the brain, and is secreted into the hemolymph to activate insulin signaling systemically. Within the brain, however, a more local activation of insulin signaling may be required to couple behavioral and physiological traits to nutritional inputs. We show that a small subset of neurons in the larval brain has high Dilp-2-mediated insulin signaling activity. This local insulin signaling activation is accompanied by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 27 publications
(33 reference statements)
1
55
0
Order By: Relevance
“…The neuroanatomy of the hugin neurons, especially exemplified by the projection pattern that connects the SOG to the protocerebrum, suggests that the SOG/protocerebrum corridor encompassing the hugin neuronal projections may play an important role in action selection of motor programs underlying feeding and locomotion (Figure 9B). The hugin projections to the protocerebrum and the connections to the gustatory cells and the insulin-producing cells [49],[78], would process external and internal sensory cues, and determine which motor programs modulating feeding and locomotion are selected.…”
Section: Discussionmentioning
confidence: 99%
“…The neuroanatomy of the hugin neurons, especially exemplified by the projection pattern that connects the SOG to the protocerebrum, suggests that the SOG/protocerebrum corridor encompassing the hugin neuronal projections may play an important role in action selection of motor programs underlying feeding and locomotion (Figure 9B). The hugin projections to the protocerebrum and the connections to the gustatory cells and the insulin-producing cells [49],[78], would process external and internal sensory cues, and determine which motor programs modulating feeding and locomotion are selected.…”
Section: Discussionmentioning
confidence: 99%
“…ILP2 is also released within the brain (Bader et al 2013). By following IPCs during larval development, we observed that IPC axons and dendrites extend over greater distances until the early third instar larval stage.…”
Section: Discussionmentioning
confidence: 99%
“…Brains were fixed in 4% paraformaldehyde for 30 min, rinsed, blocked in 5% normal goat serum, and incubated overnight at 4°C with primaries: goat anti-GFP-FITC (abcam, ab26662), 1:500; rabbit anti-DH44 (Cabrero et al, 2002) (gift of Jan Veenstra), 1:1000; guinea pig anti-Dilp2 (Bader et al, 2013) (Pankratz lab), 1:500 and rabbit anti-DMS (Schoofs et al, 1993; Park et al, 2008) (gift of Luc van den Bosch and Liliane Schoofs), 1:500. Tissues were rinsed and incubated overnight at 4°C in secondaries: anti-rabbit Alexa Fluor 633 (Invitrogen, A-21070) and anti-guinea pig Alexa Fluor 568 (Invitrogen, A-11075), both 1:500.…”
Section: Methodsmentioning
confidence: 99%